Acute left arm ischemia after TEVAR due to the anatomical variation of the vertebral artery case report = Akutna ishemija lijeve ruke nakon TEVAR-a zbog anatomske varijante vertebralne arterije : prikaz slučaja - Figl, Josip; Halužan, Damir; Pavić, Predrag, liječnik; Meštrović, Tomislav, liječnik, 1971-; Šnajdar, Irena; Papeš, Dino (2021)
Aim: In this case we report acute left arm ischemia after thoracic endovascular aortic repair of the saccular thoracic aortic aneurysm due to a rare anatomical variation of the left vertebral artery. Case report: Thoracic aortic stent-graft was deployed to cover the aneurysm, but six hours later acute left arm ischemia occurred due to a rare form of vertebral artery origin from the aortic arch instead of from the left subclavian artery. This hostile anatomy led to an iatrogenic acute ischemia which was the indication for an emergency left-common-carotid-to-subclavian-artery bypass grafting. Conclusion: Multidisciplinary approach and careful pre-procedural planning should always be the standard procedure in complex cases to avoid this complication.
Cilj: U ovom slučaju prikazujemo akutnu ishemiju lijeve ruke nakon endovaskularnog popravka sakularne aneurizme torakalne aorte nastale zbog rijetke anatomske varijacije lijeve vertebralne arterije. Prikaz slučaja: Torakalni aortni stent-graft postavljen je za rješavanje aneurizme, ali šest sati kasnije nastala je akutna ishemija lijeve ruke uslijed rijetkog položaja ishodišta lijeve vertebralne arterije luka aorte umjesto iz lijeve arterije subklavije. Ova otežavajuća anatomija dovela je do nastanka jatrogene akutne ishemije što je bila indikacija za hitnim karotiko-subklavijalnim premoštenjem. Zaključak: Multidisciplinarni pristup i pažljivo planiranje prije postupka uvijek bi trebao biti standardni postupak u složenim slučajevima kako bi se izbjegla ova komplikacija.
Bibliografija: 13 jed.
Abstract ; Sažetak.
Keywords: Aneurizma torakalne aorte -- Ishemija -- Arterije; Prikaz slučaja